(untitled) (Semiárida, 2020)
It has been compared weight gain, daily weight gain and feed gain of barrows and gilts under a differential diet, separated by sex, during fattening period, taking in to consideration the way they were housed during rearing. Sixty-four triple crossed pigs, Duroc x Jersey x Hampshire x Largewhite, in four treatments, with four repetitions for treatment and with four animals for repetition were used. Gilts that have been housed with other gilts since weaning, and which were supplied with a 14% B.P. diet during fattening, had a higher weight gain (51,37 kg vs. 40,94, 41,65 kg) daily weight gain (0,917 vs. 0,731 and 0, 744 kg); and feed/gain (3,52:1 vs, 4,57:1 and 4,40:1) highly significative with regard to gilts that were housed with males during rearing and afterwards only with gilts with a 13% and 14% protein level on the diet, respectively. Significate differences were also experimented with the sample lot (males housed with gilts during rearing, alone during fattening with a 13% B.P. diet. The sample lot showed favorable significative differences with regard to gilt groups which were housed with males during rearing, suppling afterwards a 13% and 14% B.P. diet, respectively, on fattening period. It ls is recommended to separate boars since weaning from the barrow lots and to supply a differential diet in the finishing period.